Tattoos on Instagram : how the platform connects professionals and consumers - Silva, Maria Catarina Amado e Vasconcelos Duarte (2022)
The object of study of this dissertation is the relationship created through Instagram between tattoo artists and consumers. This investigation emphasizes how the relationship allows artists to position themselves in this social network, its advantages, and the reasons that lead a consumer to get a tattoo. The relevance of the same is because few studies investigate the consumption of tattoos in Portugal, the connection that followers create on Instagram with tattoo artists and the impact that this has on the consumption of tattoos. As for the methodological choice, it is a mixed study. That involved the qualitative analysis of the data collected from content analysis and interviews with 6 tattoo artists, as well as the quantitative analysis of the data collected from a questionnaire answered by 567 tattoo consumers on Instagram. It is concluded that tattoo artists connect with their followers on Instagram by sharing personal content that allows identification by consumers. The reasons for consumers to follow tattoo artists are entertainment search and identification, and they interact with them mainly through private messages, answering polls on Instagram stories, comments and likes.